Výskyt ošetrovateľských diagnóz u pacientov s nutričnou jejunostómiou - Hlinková, Edita; Nemcová, Jana; Slezáková, Monika (Ošetrovateľstvo, 2016)
Aim: The aim of the study was to identify nursing diagnosis of patients who underwent placement of feeding jejunostomy. Then compare the differences in the incidence of nursing diagnosis in terms of indication jejunostomy introduction, surgical diagnosis and age. Methods: A retrospective study was performed of patients underwent of feeding jejunostomy for carcinoma oesophagus, stomach and biliary tract. Participants were divided in two groups: I. group of patients after radical surgery treatment of temporary postoperative enteral nutrition through jejunostomy and II. group of respondents with inoperable malignant process with the introduction of nutritional jejunostomy. The main tool of research, we used content analysis patient's medical records, including nursing documentation (operating and 7th postoperative day). We have developed a research protocol of its own design. Jejunostomy feeding problems were divided into four categories: infectious, gastrointestinal, metabolic and mechanical complications. Results: We recorded the occurrence of nursing diagnosis, but without statistical significance in terms of the type of indication jejunostomy. Of the total 53 respondents had deficient fluid volume 91 %, over half of the respondents had pain around the catheter (58 %), hyperthermia (64 %) and 13 % had impaired the integrity of the skin around the catheter. We have seen a high incidence of gastrointestinal complications: diarrhea (49 %), nausea (80 %), abdominal pain (96 %). We have also identified a number of important defining characteristics as redness around the catheter in 4 % of patients, heperglycemia 28 % and 32 % hypocalemia. In terms of age of the respondents we obtained a statistically significant results in the occurrence of pressure sores around the catheter – impared integrity due to the presence of the catheter (p = 0.04). Conclusion: Jejunostomy is safe maintenance performance combined with a low incidence of postoperative infectious and metabolic complications compared to total parenteral nutrition, although also not without risk. Of the most common nursing problems they have been diagnosed with diarrhea, nausea, hyperthermia, acute pain and deficient fluid volume.
Keywords: ošetřovatelská diagnóza; lidé; ženské pohlaví; Jejunostomy; senioři nad 80 let; jejunostomie; Humans; Aged; Female; senioři; Nursing Diagnosis; mužské pohlaví; Male; Aged, 80 and over; enterální výživa; Enteral Nutrition